B1 bradykinin receptors and sensory neurones. - Davis, C. L. (1996)
1. The location of the B1 bradykinin receptors involved in inflammatory hyperalgesia was investigated. 2. No specific binding of the B1 bradykinin receptor ligand [3H]-des-Arg10-kallidin was detected in primary cultures of rat dorsal root ganglion neurones, even after treatment with interleukin-1 beta (100 iu ml-1). 3. In dorsal root ganglion neurones, activation of B2 bradykinin receptors stimulated polyphosphoinositidase C. In contrast, B1 bradykinin receptor agonists (des-Arg9-bradykinin up to 10 microM and des-Arg10-kallidin up to 1 microM) failed to activate polyphosphoinositidase C, even in neurones that had been treated with interleukin-1 beta (100 iu ml-1), prostaglandin E2 (1 microM) or prostaglandin I2 (1 microM). 4. Dorsal root ganglion neurones removed from rats (both neonatal and 14 days old) that had been pretreated with inflammatory mediators (Freund's complete adjuvant, or carrageenan) failed to respond to B1 bradykinin receptor selective agonists (des-Arg9-bradykinin up to 10 microM and des-Arg10-kallidin up to 1 microM). 5. Bradykinin (25 nM to 300 nM) evoked ventral root responses when applied to peripheral receptive fields or central terminals of primary afferents in the neonatal rat spinal cord and tail preparation. In contrast, des-Arg9-bradykinin (50 nM to 500 nM) failed to evoke ventral root depolarizations in either control rats or in animals that developed inflammation following ultraviolet irradiation of the tail skin. 6. The results of the present study imply that the B1 bradykinin receptors that contribute to hypersensitivity in models of persistent inflammatory hyperalgesia are located on cells other than sensory neurones where they may be responsible for releasing mediators that sensitize or activate the nociceptors.